The study of plant Sambucus Ebulus l. (Caprifoliaceae) from spontaneous flora- and its benefic obtained effects - Sorin Jianu; Daniela Laura Buruiană; Ștefania Eliza Tănasie; Alexandru Chiriac (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
In this paper, the authors had presented a study made on the leaves of Sambucus ebulus L. and they tried to give a higher trust of naturist products, especially because these are plants from the spontaneous flora of our country. Because the results obtained over the time from these plants are satisfactory, with the condition of rational consumption, the determinations made at this plant fit in normal ranges, in order to be used with trust, especially against constipation and emetic in certain cases [Olimpia Pandia., Sæaræacin I, Dinu Mariana, Chiriac Al.,]. The marketing of these products, in different forms, also comes to complete a sure income and easy to be obtained.
Keywords: 330; flora; spontaneous; chlorophyllian pigments; naturist product